FAKTOR RESIKO KEJADIAN KEHAMILAN EKTOPIK TERGANGGU DI RS.PEKANBARU MEDICAL CENTER PEKANBARU TAHUN 2021 - Ihsan Suheimi; Mona Dewi Utari (Ensiklopedia of Journal, 2023)
Maternal mortality rate (MMR) in Indonesia is still very high. Deaths that occurred before labor, among others, caused by abortion and Ectopic pregnancy. Ectopic pregnancy occurs 4-5 events in 1000 births and was ranked seventh in the 15 cases in 2021 in hospitals Pekanbaru Medical Center Pekanbaru. The purpose of this study to determine the incidence of risk factors Ectopic Pregnancy Plagued with descriptive research design. The research was carried out in Pekanbaru Medical Center population was all patients with bleeding cases in the first trimester of pregnancy were treated in Melati Pekanbaru Medical Center Hospital in 2021 as many as 57 cases. Sample collection technique is the total sampling studies rekammedis record documentation. Univariate analysis was used with the manual processing and are presented in a frequency distribution table of the results of the study in 66.7% of pregnant women.